Role of experts of the social sphere in improvement of the humanistic maintenance of the public relations (The Journal of Psychology and Sociology, 2012)
The social sphere is the key sphere of society. Experts of this sphere play large role in a society humanization. Forma- tion of civil society and the social state is an actual problem in modern conditions. Experts of the social sphere actively participate in formation of model of civil society, the social state. Social protection of poor layers sectors of society, devel- opments of their personal qualities, self-esteem, improvement of forms and ways of social support of the population is of great importance from the strategic point of view. It demands the accounting of specifics of development of Kazakhstan as national state in the course of planning of the purpose of social development.
Keywords: social; civil society; the welfare state; social protection.